Low-dose nafamostat mesilate ameliorates tissue injury and inhibits 5-hydroxytryptamine synthesis in the rat intestine after methotrexate administration - Takahiro Yamamoto; Takuji Machida; Chiho Tanno; Shiori Hasebe; Mayu Tamura; Nanaka Kobayashi; Sachiko Hiraide; Naoya Hamaue; Kenji Iizuka (Elsevier, 2023)
We aimed to clarify the effect of nafamostat mesilate (nafamostat) on intestinal mucositis as well as the potentiation of intestinal 5-hydroxytryptamine (5-HT) dynamics induced by methotrexate, an anti-cancer drug, in rats. Rats received intraperitoneal methotrexate at 12.5 mg/kg/day for 4 days. In addition, 1, 3, or 10 mg/kg/day of nafamostat was given subcutaneously for 4 days. Ninety-six hours after the first administration of methotrexate, jejunal tissues were collected for analysis. The results showed that 1 mg/kg, but not 3 or 10 mg/kg, of nafamostat significantly ameliorated the methotrexate-induced body weight loss. Moreover, 1 mg/kg of nafamostat significantly improved methotrexate-induced mucositis, including villus atrophy. Nafamostat (1 mg/kg) significantly inhibited the methotrexate-induced mRNA expression of pro-inflammatory cytokines and cyclooxygenase-2, as well as methotrexate-induced 5-HT content and tryptophan hydroxylase (TPH) activity. In addition, it tended to inhibit the number of anti-TPH antibody-positive cells and significantly inhibited the number of anti-substance P antibody-positive cells. These findings suggest that low-dose nafamostat ameliorates tissue injury and 5-HT and substance P synthesis in methotrexate-induced mucositis. Nafamostat may be a novel therapeutic strategy for the prevention and treatment of mucositis as well as 5-HT- and/or substance P-related adverse effects in cancer chemotherapy.